Adsorption and purification performance of lysozyme from chicken egg white using ion exchange nanofiber membrane modified by ethylene diamine and bromoacetic acid. (1st October 2021) - Chang, Yu-Kaung; Cheng, Hsing-I; Ooi, Chien Wei; Song, Cher Pin; Liu, Bing-Lan
Highlights: A simple method was developed for preparation of polyacid nanofiber membrane. P-BrA was very selective in adsorbing lysozyme from CEW. Lysozyme was recovered by 0.6 M NaCl with PF = ~402 and RY = ~91%. Abstract: A high-performance polyacid ion exchange (IEX) nanofiber membrane was used in membrane chromatography for the recovery of lysozyme from chicken egg white (CEW). The polyacid IEX nanofiber membrane (P-BrA) was prepared by the functionalization of polyacrylonitrile (PAN) nanofiber membrane with ethylene diamine (EDA) and bromoacetic acid (BrA). The adsorption performance of P-BrA was evaluated under various operating conditions using Pall filter holder. The results showed that optimal conditions of IEX membrane chromatography for lysozyme adsorption were 10% (w/v) of CEW, pH 9 and 0.1 mL/min. The purification factor and yield of lysozyme were 402 and 91%, respectively. The adsorption process was further scaled up to a larger loading volume, and the purification performance was found to be consistent. Furthermore, the regeneration of IEX nanofiber membrane was achieved under mild conditions. The adsorption process was repeated for five times and the adsorption capacity of adsorber was found to be unaffected.